Effect of Cryoprotectants and Low Temperatures on Survival of Bovine, Equine and Rabbit Erythrocytes - Ulizko, Pavel Yu.; Bobrova, Elena N. (Problems of Cryobiology and Cryomedicine, 2016)
Probl Cryobiol Cryomed 2016; 26(2):184.